PENGARUHPENERAPAN STRATEGI GIVINGQUESTIONSAND GETTING ANSWER (GQGA) TERHADAPPEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 11 SOLOK SELATAN - Gustina, Deni Marion; Anggraini, Villia; Fitri, Dewi Yuliana (STKIP PGRI Sumbar, 2013)
This research based on isconceptual mathematic studentsâ comprehension which still low. One way to increase the conceptual mathematic student by using GivingQuestionsand Getting Answer (GQGA) strategy. This research was done to know how student activity in applying GivingQuestionsand Getting Answer (GQGA) strategy in mathematic learning and the influenceof applying GivingQuestionsand Getting Answer (GQGA) strategy on conceptual mathematic students comprehension. This research use experimental research, which used subject random. The instrument which is used in this research was final test in essay formed with test reability r11 = 0,88. The technique of data analysis was t-test straightly. The result of hypothesis test was receivedÎ± = 0,05Â and hypothesis tests was, so hypothesis was accepted. It can be concluded that the comprehension of conceptual mathematic student in applying GivingQuestionsand Getting Answer (GQGA) strategy is better than comprehension of conceptual student in conventional learning.Â